Worker information systems including dynamic visualisation: A perspective for minimising the conflict of objectives between a resource-efficient use of inspection equipment and the cognitive load of the worker - Lušić, Mario; Braz, Konrad Schmutzer; Wittmann, Stephan; Fischer, Christian; Hornfeck, Rüdiger; Franke, Jörg (Advanced Materials Research, 2014)
In the context of casting mould inspection, the conventional paper-based provision of information for workers can be characterised by a conflict of objectives. On the one hand, a minimisation of the cognitive load of the worker is desirable. To this end the inspection procedure is oriented on the complete processing of each view of the single-part drawing. This leads to a necessary change between inspection devices within individual views. On the other hand, a resource-efficient use of inspection equipment is desirable. To this end, the inspection tasks are grouped so that for each group one single inspection device is assigned. This requires a change between the views of the single-part drawing within each inspection device, which increases worker’s cognitive load. By means of a realistic representation of the inspection operations to be carried out, by using a Worker Information System which is based on animated graphical representations (dynamic visualisation), the increase of the cognitive load that is caused by the resource-efficient use of inspection equipment could be compensated.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Inspection; Quality assurance; Worker information system